PERMAINAN PERANG AIR (CHIAN-CUI) PADA PERAYAAN IMLEK DI SELATPANJANG - Aiditya, Rizki; Melay, Ridwan; ', Kamarudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The game is the creation of a water fight in the celebration of Chinese New Year in Selatpanjang. With the game of water war (Chian-CUI) in Selatpanjang able to add an air of excitement and entertainment in celebration of the Chinese New Year. It was proved by the increasing local and foreign tourists every year when entering the Chinese New Year celebration to visit Selatpanjang to see the excitement contained in Selatpanjang when entering the Chinese New Year celebrations, which will not be felt in other areas. The purpose of this study was to determine the Chinese tradition in Selatpanjang. To find out the background for the game of water war (Chian-CUI) at a Chinese New Year celebration in Selatpanjang. To find out how the development of water wargame (Chian-CUI) at a Chinese New Year celebration in Selatpanjang. To determine the value terkadung water fight during the game (Chian-CUI) at a Chinese New Year celebration in Selatpanjang. To determine the effect of water wars game (Chian-CUI) to the Chinese New Year celebrations in Selatpanjang. To determine the impact of positive and ngeatif water war games (Chian-CUI) at the time of the celebration Imlwk in Selatpanjang. The method used in this study is historical and qualitative methods. Data were obtained from interviews later in the analysis in its own language. The research sites are in town Selatpanjang Meranti Islands District. When the study started from the seminar proposal until a thesis seminar. Data collection techniques used were observation, interview techniques, technical documentation and technical literature. From research it has been found that the water wargame (Chian-CUI) is a game to be held for six days from the first day until the sixth day of the Lunar Lunar played on a motor rickshaw to surround these wars. Water war games have long played by the public Selatpanjang children terkhususnya Malay community, but only the last few years developed by Chinese young people as creations in the celebration of Chinese New Year in Selatpanjang.Keywords: Water War Game (Chian-Cui), Lunar, Selatpanjang